Internalisasi Nilai Karakter Toleransi Melalui Media Poster Keragaman pada Pembelajaran Pendidikan Kewarganegaraan di Sekolah Dasar - Rijal, Akmal; Mulyono, Dodik; Pratama, Aldora (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to develop a method for internalizing tolerance character values through diversity posters in Civic Education learning at the elementary school level. The research utilized the analysis, development, implementation, and evaluation model. The subjects of this study were 80 fifth-grade students from SD Negeri 42 Lubuklinggau, comprising 65 females and 25 males from diverse religious, cultural, and linguistic backgrounds. The instruments used included tolerance character observation sheets, validation questionnaires, practicality questionnaires, and essay test questions. Data were analyzed using Aiken’s V, percentage analysis, and paired sample tests. In the development stage, needs analysis, media selection, and poster design on religious diversity were conducted using Canva. Validity results showed an Aiken’s V score of 0.91, categorized as valid. The practicality of this method received a score of 88.49%, classified as highly practical. The effectiveness test indicated an increase in the average pretest score from 74.4750 to 77.6000 in the posttest, with a significance value (Sig. 2-tailed) of 0.000, less than 0.05. Observations of tolerance character showed an indicator of 79%, classified as high. Thus, this study produced a final product in the form of a valid, practical, and effective method for internalizing tolerance character values through diversity posters in Civic Education learning at the elementary school level.